2019
DOI: 10.1108/itp-07-2017-0216
|View full text |Cite
|
Sign up to set email alerts
|

Exploring player behavior and motivations to continue playing Pokémon GO

Abstract: Purpose The purpose of this paper is to identify the determinants of players’ continuance intentions to play Pokémon GO (PG) and ultimately make in-app purchases, mainly from the perspectives of psychological, social and gaming motivational factors. Design/methodology/approach The research model was empirically assessed based on 362 validated responses from current players of PG in Malaysia. Analysis was carried out using the partial least squares path modeling method. Findings The results indicated that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
85
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 80 publications
17
85
1
Order By: Relevance
“…In gaming research, the term has been used synonymously with task continuance (Huang et al, 2017;Liao et al, 2016), continued intention to use (M.-C. Lee & Tsai, 2010), sustained use (Wohn, 2013), and loyalty (Choi & Kim, 2004;Teng & Chen, 2014). Prior research has typically focused on modeling the factors that keep people playing an online game (Chang et al, 2014;Ghazali et al, 2018;Li et al, 2015;Liang & Yeh, 2011;Nguyen, 2015) or hinder continuance intention (Liao et al, 2016). Findings suggested that higher satisfaction (Anderson & Srinivasan, 2003;Bhattacherjee, 2001), perceived enjoyment (Davis et al, 1992;M.-C. Lee & Tsai, 2010;Merikivi et al, 2017;Nguyen, 2015;Wu et al, 2010), disconfirmation of expectations (Liao et al, 2016), and social connection (Ryan et al, 2006;Teng & Chen, 2014;Wu et al, 2010) are common drivers of continuance intention.…”
Section: Continuance Intentionmentioning
confidence: 99%
“…In gaming research, the term has been used synonymously with task continuance (Huang et al, 2017;Liao et al, 2016), continued intention to use (M.-C. Lee & Tsai, 2010), sustained use (Wohn, 2013), and loyalty (Choi & Kim, 2004;Teng & Chen, 2014). Prior research has typically focused on modeling the factors that keep people playing an online game (Chang et al, 2014;Ghazali et al, 2018;Li et al, 2015;Liang & Yeh, 2011;Nguyen, 2015) or hinder continuance intention (Liao et al, 2016). Findings suggested that higher satisfaction (Anderson & Srinivasan, 2003;Bhattacherjee, 2001), perceived enjoyment (Davis et al, 1992;M.-C. Lee & Tsai, 2010;Merikivi et al, 2017;Nguyen, 2015;Wu et al, 2010), disconfirmation of expectations (Liao et al, 2016), and social connection (Ryan et al, 2006;Teng & Chen, 2014;Wu et al, 2010) are common drivers of continuance intention.…”
Section: Continuance Intentionmentioning
confidence: 99%
“…The gaming industry has recently been transformed by introducing innovative technologies (Ghazali et al, 2019). Consequently, the revenues from online gaming have increased tremendously (Teng, 2017), and it is predicted that this industry will develop into a multibillion dollar international industry (Werder et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a general way, online games are one type of hedonic ICT [23,53,[56][57][58][59]. Users can alleviate boredom by playing games linked with mobile phones [60].…”
Section: Research Modelmentioning
confidence: 99%